2013
DOI: 10.1111/tmi.12059
|View full text |Cite
|
Sign up to set email alerts
|

Response patterns to interactive SMS health education quizzes at two sites in Uganda: a cohort study

Abstract: Abstractobjective The use of mobile phones can improve and strengthen (preventive) health care in lowand middle-income countries. We aimed to retrospectively assess the response patterns of participants in free SMS health education quizzes in Uganda.methods Study participants were employees of two companies and their community networks. We investigated how quickly individuals responded to quiz question(s) and assessed possible influencing factors. Cox regression and ANOVA analyses were used.results Fifty perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…[30,31] Demographic information regarding the users of these platforms was not included thus making it difficult to assess the representativeness of respondents. Two studies attempted to achieve a subnational sample through opt-in recruitment, potentially introducing selection bias [32,33]. Numerous studies used SMS and IVR surveys as a data collection tool within a research study [34-54] or as a surveillance instrument for health care workers [55-59] and were excluded from the review.…”
Section: Resultsmentioning
confidence: 99%
“…[30,31] Demographic information regarding the users of these platforms was not included thus making it difficult to assess the representativeness of respondents. Two studies attempted to achieve a subnational sample through opt-in recruitment, potentially introducing selection bias [32,33]. Numerous studies used SMS and IVR surveys as a data collection tool within a research study [34-54] or as a surveillance instrument for health care workers [55-59] and were excluded from the review.…”
Section: Resultsmentioning
confidence: 99%
“…While a previous study in Uganda reported a 70% response rate to SMS containing health education quizzes [31], another large study conducted in northern Uganda involving a one-time SMS intervention found that only 23% responded, similar to what we observed in our study [32]. Although a widely cited systematic review has previously shown that two-way SMS are more effective than one-way SMS in engaging patients [33], the focus of that review was on longitudinal SMS interventions for medication adherence, not on responses to a one-time communication.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown higher levels of engagement when utilizing serial messaging and two-way communications [6,7,34,35], rather than one-time messaging. Including quizzes or trivia may also improve participant response rates [31]. These strategies, along with more personalized SMS content [21], may increase participant engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is insufficient evidence on facilitators and barriers to the use of mobile phones for health-related needs (Chib, Wilkin and Hoefman 2011). Besides inadequate knowledge of how the new service works and what benefits are of using it (Marwa et al 2013), reasons for non-use of mobile phones have been linked to privacy concerns and network coverage (Chib et al 2012;Lepper et al 2013).…”
Section: Utilization and Accessmentioning
confidence: 99%